LEARNING LOSSES AMONG STUDENTS OF GENERAL SECONDARY SCHOOLS IN UKRAINE AS A CONSEQUENCE OF UNPREDICTABLE GLOBAL CHALLENGES: CHALLENGES AND PERSPECTIVES - Topuzov, Oleh; Malykhin, Oleksandr; Aristova, Nataliia; Kalinina, Liudmyla; Mosiakova, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the context of a full-scale war in Ukraine launched by Russia on February 24, 2022, Ukraine’s educational system in general and the system of general secondary education in particular faced previously unforeseen challenges in organising educational process under martial law. These challenges lead to the emergence of previously unpredictable problems in the system of general secondary education that require systemic and purposeful solutions. One of these problems is directly related to learning losses among students of general secondary education and the search for effective ways of compensating for these learning losses. And although learning losses have become an objective reality at all levels of education, this issue is especially true in general secondary education institutions, as school-age children are the most vulnerable in the context of the tragic events taking place in Ukraine due to the war. Taking into account the fact that this topic has not been systematically studied in the scientific literature, the present paper is aimed at identifying war-related learning losses based on the experience of Ukrainian general secondary school teachers. The data collection instrument includes a questionnaire developed by the authors of this paper and the research sample includes 352 general secondary school teachers.